2016
DOI: 10.1080/07373937.2016.1201486
|View full text |Cite
|
Sign up to set email alerts
|

Foam mat drying of mango: Effect of processing parameters on the drying kinetic and product quality

Abstract: This study investigated the foam mat drying process parameters (temperature and concentration of foaming agents, albumin, and an emulsifier blend) and evaluated their effects on drying kinetics, color, carotenoid retention, and solubility of the mango pulp powder. Fick's model was able to represent the foam mat drying kinetics. The foaming agents and high temperatures enhanced the carotenoid retention. This was explained by the greater effective water diffusion coefficients that allowed obtaining products with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 43 publications
5
22
0
1
Order By: Relevance
“…These results are in agreement with those reported by Chaux‐Gutiérrez et al. (2017) in mango foam mat drying, Maciel, Afonso, Costa, Severo, and Lima (2017) for guava, and Dehghannya et al. (2018a) for lime juice.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These results are in agreement with those reported by Chaux‐Gutiérrez et al. (2017) in mango foam mat drying, Maciel, Afonso, Costa, Severo, and Lima (2017) for guava, and Dehghannya et al. (2018a) for lime juice.…”
Section: Resultssupporting
confidence: 92%
“…Chaux‐Gutiérrez et al. (2017) also observed that temperature was the factor with the most significant effect on D eff in mango foam mat drying.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Table 3 shows the chroma, hue angle, and browning index values of foam-dried aquafaba powder at different drying temperature conditions. Chroma and hue angle is of major significance in color properties due to represent both tonality and bright of aquafaba powders after different drying temperature conditions (Chaux-Gutiérrez et al, 2017). Chroma values of aquafaba powder were calculated and ranged between 22.40 and 24.26.…”
Section: Color Propertiesmentioning
confidence: 99%